PEMBUATAN CEMILAN BERBAHAN SAGU OLEH SEKELOMPOK IBU-IBU DARI KELURAHAN YABANSAI KOTA JAYAPURA - Ilham Salim; Supeno Supeno (LPPM Uncen, 2022)
Sago is a plant that has high nutritional value if it is processed according to production standards. Sago contains the Glycemic Index so it is very good for health, especially for diabetics. The process of making sago snack production in the form of training conducted in Yabansai Village, Heram District, Jayapura City. The method used was the participatory observation method of the object where the lecturer team implementing the activities and the training participants observe and were directly involved (face to face) in each step of their work. In addition, interviews were conducted with community service supervisors with target fields who were PKK mothers who had spare time and had not yet been used to produce something of added value to their family's economy. The activity began with a lecture related to the health benefits of sago as well as a lecture on the implementation instructions for the process of making sago snacks from the preparation of ingredients to the mixing and frying process of snack ingredients and ending with packaging. The end result of this activity provides benefits for activity participants to know and understand that the sago material consumed can be beneficial for health. Participants were also motivated to make sago snack businesses both individually and in partnership to open jobs, especially for those who have spare time and have been wasted so far. Participants understood that if a business wants to grow, it must have a permit from BPOM and a halal certificate from MUI. The important thing that impacts at least two things, 1) preservation of the source of sago material (sago tree) as a typical plant that is only found in certain areas.2) the use of sago raw materials to become a snack product with high economic value and in turn it can create jobs for the general public. Keywords: Sago; health; snacks; participants; motivated; business unit